2008
DOI: 10.1186/ar2549
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of repair tissue in second-look and third-look biopsies from patients treated with engineered cartilage: relationship to symptomatology and time after implantation

Abstract: IntroductionThe present study established characteristics of tissue regrowth in patients suffering knee lesions treated with grafts of autologous chondrocytes grown on three-dimensional hyaluronic acid biomaterials.MethodsThis multicentred study involved a second-look arthroscopy/biopsy, 5 to 33 months post implant (n = 63). Seven patients allowed a third-look biopsy, three of which were performed 18 months post implant. Characteristics of tissues were histologically and histochemically evaluated. The remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 27 publications
9
72
0
2
Order By: Relevance
“…The first aspect is the time frame of matrix production in our model. The time frame of 18 months for a defect to reach full maturation after chondrocyte implantation corresponds with results from a recent clinical study of patients treated with autologous chondrocytes seeded in a hyaluronan-based polymer (Brun et al (2008)). The analysis of 70 biopsies from 63 patients in that study, taken between 5 months and 333 months after surgery, demonstrated that cartilage regeneration is a slow process taking around 18 months.…”
Section: Discussionsupporting
confidence: 60%
“…The first aspect is the time frame of matrix production in our model. The time frame of 18 months for a defect to reach full maturation after chondrocyte implantation corresponds with results from a recent clinical study of patients treated with autologous chondrocytes seeded in a hyaluronan-based polymer (Brun et al (2008)). The analysis of 70 biopsies from 63 patients in that study, taken between 5 months and 333 months after surgery, demonstrated that cartilage regeneration is a slow process taking around 18 months.…”
Section: Discussionsupporting
confidence: 60%
“…At the time of its implantation, the Hyalograft-C graft contains chondrocytes attached to the Hyaff-11 mesh fibers, but little to no extracellular matrix, and thus, maturation of the implanted construct (biochemically and mechanically) occurs within the repair site [17], typically taking more than 18 months [18]. While a graft with negligible mechanical properties may be sufficient for filling focal defects, in which the surrounding healthy native cartilage may be sufficient to support joint loading, a graft for resurfacing the lateral or medial condyle would likely need to be at a more advanced stage of maturation to provide a higher degree of functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CS chains were significantly shorter in 12 month ACI repair tissue 8 . Many studies have reported on maturation of chondrocytes in pellets 31 and cartilage like tissue in scaffolds 32 but very few studies have reported on tissue maturation within a cartilage defect 11,12,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Basic histological studies of ACI biopsies indicate that repair tissue matures slowly [11][12][13] . Further detailed studies are necessary to fully assess the molecular characteristics of the tissue as it matures over time.…”
Section: Introductionmentioning
confidence: 99%